7.1 Spangenberg - Sampling Standards In Anglogold Ashanti Gold Mines In Sa - Conné Spangenberg (The Southern African Institute of Mining and Metallurgy, 2005)
Contents ?Introduction ?Metal accounting environment ?Problem statement ?Investigations & Achievements ?Metal Accounting ?Principles ?Standards ?Audits ?Questions